Dissecting the cellular components of ex vivo γδ T cell expansions to optimize selection of potent cell therapy donors for neuroblastoma immunotherapy trials. (31st December 2022) - Jonus, Hunter C.; Burnham, Rebecca E.; Ho, Andrew; Pilgrim, Adeiye A.; Shim, Jenny; Doering, Christopher B.; Spencer, H. Trent; Goldsmith, Kelly C.
ABSTRACT: γδ T lymphocytes represent an emerging class of cellular immunotherapy with preclinical promise to treat cancer, notably neuroblastoma. The innate-like immune cell subset demonstrates inherent cytoxicity toward tumor cells independent of MHC recognition, enabling allogeneic administration of healthy donor-derived γδ T cell therapies. A current limitation is the substantial interindividual γδ T cell expansion variation among leukocyte collections. Overcoming this limitation will enable realization of the full potential of allogeneic γδ T-based cellular therapy. Here, we characterize γδ T cell expansions from healthy adult donors and observe that highly potent natural killer (NK) lymphocytes expand with γδ T cells under zoledronate and IL-2 stimulation. The presence of NK cells correlates with both the expansion potential of γδ T cells and the overall potency of the γδ T cell therapy. However, the potency of the cell therapy in combination with an antibody-based immunotherapeutic, dinutuximab, appears to be independent of γδ T/NK cell content both in vitro and in vivo, which minimizes the implication of interindividual expansion differences toward efficacy. Collectively, these studies highlight the utility of maintaining the NK cell population within expanded γδ T cell therapies and suggest a synergistic action of combined innate cell immunotherapy toward neuroblastoma.